LA PRESENTACIÓN DE PRUEBA NUEVA EN LA AUDIENCIA DEL JUICIO, VULNERA EL DERECHO A LA DEFENSA Y AL DERECHO DE CONTAR CON EL TIEMPO Y CON LOS MEDIOS ADECUADOS PARA LA PREPARACIÓN DE SU DEFENSA” - Tenesaca García, Pablo Andrés (2020)
The present thesis entitled: "THE PRESENTATION OF NEW PROOF AT THE TRIAL HEARING, VULNERS THE RIGHT TO THE DEFENCE AND THE RIGHT TO COUNT WITH THE TIME AND WITH MEANS ADEQUATE FOR THE PREPARATION OF YOUR DEFENSE" arises when in traffic violations, the offender at the time of contesting the citation issued by the traffic officer, must present evidence at the proper procedural time established i.e. three days before the trial hearing; On the contrary, the transit agent does it in the trial hearing, leaving without effect two of the principles that govern the announcement and the practice of evidence, such as the principle of contradiction and the principle of equal opportunities for the evidence; allowing us to consider the evidence of the transit agent as new evidence since it is not part of the process; because the evidence provided by the agent is known at that moment, in addition as most are photos and videos, can be altered, because they do not apply chain of custody as determined by the Comprehensive Organic Code of Criminal Law for all digital content. However, it has negative aspects that affect constitutional principles, including the fact that the alleged offender must announce the evidence up to three days before the hearing, while the transit agent does so at the trial hearing, which puts the parties in a situation of inequality, but notwithstanding this, from the moment of the commission of the infraction until the day of the hearing, the evidence is in the possession of the traffic agent, which means that it loses the evidentiary effectiveness required by law, because it is generally known that evidence must be obtained by court order, be lawful and may be challenged by the offender, must be presented in its original state, which in this type of case, is obvious, even in court has been heard the agents say that the video is "cut". How 9 is this possible? When the law establishes that they cannot be edited, decontextualized or manipulated if so, they must be declared invalid leaving evidence that in the expedited procedure in traffic contraventions, it violates fundamental rights of the parties because they do not have enough time and means to exercise the right to defense. For the development of the present investigative topic, the general objective was proposed, which is to carry out a study of a legal, doctrinal, social and comparative nature, with respect to the evidence presented by the civil transit agent, in expedited procedure for traffic violations, as well as three specific ones; the first to demonstrate that the offender's right to technical defense is violated in the expedited judicial process for traffic violations, by introducing unannounced evidence by the civil transit agent in the trial hearing; The second is to establish that the application of unannounced evidence in the expedited procedure for traffic violations may be altered or modified; and the third is to draft a reform of the Comprehensive Organic Penal Code to guarantee the rights of offenders within the trial hearing, which have been complied with in the development of this investigation. The theoretical, legal and doctrinal collection, the application of surveys, interviews, comparative law and case studies made it possible to promote a discussion of the subject with different points of view, giving clear and precise results to propose a project to reform the Comprehensive Organic Penal Code, so that the civil transit agent presents the evidence under the same conditions as the alleged offender would be, announcing the evidence up to three days before the hearing.